PENGARUH ORIENTASI PASAR DAN ORIENTASI KEWIRAUSAHAAN TERHADAP INOVASI PRODUK DAN KEUNGGULAN BERSAING UMKM JENANG DI KABUPATEN KUDUS - Muhamad Zidni Syukron; Ngatno Ngatno (Jurnal Ilmu Administrasi Bisnis, 2016)
The company's success to maintain the sustainability of their products sales lies inthe ability to have a strategy or innovative thinking by seeing on market orientationand entrepreneurial orientation, and having a strong competitive advantage. Thisresearch is conducted to determine the influence of market orientation andentrepreneurial orientation toward product innovation and competitive advantagein Jenang Micro, Small and Medium Enterprises (SMEs) of Kudus Regency. Thistype of research is explanatory research. The sampling techniques used totalsampling that is overall Jenang SMEs owner of Kudus Regency. The respondentsin this research totaled 43 respondents. Collecting data used questioner, with scorestart from 1 (very disagree) to 5 (really agree). This research was also using Pathanalysis techniques supported by SPSS (Statistical Package for Social Science)software version 20.3. The validity test, reliability test, coefficient of correlationtest, coefficient of determination test, linear and multiple regression, significancetest (t and F test) and Sobel method beforehand. The results showed that allindependent variables in this study had a significant influence on the dependentvariable, either partially or simultaneous, product innovation acts as a partialmediating variable, that indicates an indirect effect of variables of marketorientation and entrepreneurial orientation on competitive advantage.